Служба волинських православних священиків в органах єпархіального управління та виконання ними архієрейських доручень (перша половина ХІХ ст.) - Боярчук, Андрій Володимирович; Boyarchuk, Andrei (Східноєвропейський національний університет імені Лесі Українки, 2016)
У статті на основі мікростатистичного аналізу клірових відомостей показано задіяність волинських єреїв у роботі єпархіального управлінського апарату та виконання ними архієрейських доручень у першій половині ХІХ ст. Схарактеризовано устрій органів управління Православної церкви на Волині у визначений період.On the basis of analysis mikrostatistic Klirovye informative statements shows the involvement of Volyn Diocesan priests in the work of the administrative apparatus and the performance of episcopal orders in the first half of the XIX century. It is characterized by a device of the Orthodox Church administration in the Volyn region in a certain period. It was found that in the first half of the XIX century, a small amount of Volyn priests were involved in the work of the diocesan agencies ecclesiastical authority.
Service Volyn Orthodox Priests in Diocesan Administration and Execution of Orders Priests Episcopal Bodies (First Half of the XIX Century)
Keywords: Волинська єпархія; клірові відомості; духовна консисторія; духовне правління; благочиння; Volyn Diocese; klirovye statements; spiritual consistory; spiritual board; deanery